Птицы родного края: иллюстрированная энциклопедия / под ред. Е. В. Зубакиной - Зубакиной Е.В. (ОЛЛИС, 2010)
Экземпляры: ф.15 (03.02.2012) / Инвентарный номер: 46601 / Цена: 300 / Авт.знак: П 87 / ГРНТИ: 34.33 / ББК: 28.693.35